Web Service untuk Integrasi Data dalam Pengelolaan Data Potensi Prestasi Mahasiswa STMIK Amikom Purwokerto - Andik Wijanarko; Dwi Ngafifuddin (LPPM STMIK Widya Utama, 2017)
The student achievement data is included in the standard of three of accreditation forms. Achievement data and potential of students are needed in order to accreditation and other purposes such as inputs in the guidance of students to achieve achievement. STMIK Amikom Purwokerto already has data related to student achievement and potential. However, the data is spread over several application databases such as the Academic Information System Application and the New Student Admission Application. This study aims to build applications that integrate existing data in some of these databases to form a new database. This database is used to manage potential data and student achievement. The Webservice method is used in order not to change the existing database structure on the Server. The JSON data format is used to transmit data from the Database Server to the Client database. The results of this research is a potential data processing application and student achievement that is integrated with several other databases with Webservice method and JSON data format. PHP programming language used to build applications and call web service with CURL function in PHP.